Serum copper and caeruloplasmin in ankylosing spondylitis, systemic sclerosis, and morphea. Issue 5 (October 1976) - Jayson, M. I. V.; Davis, P.; Whicher, J. T.; Walters, G.
Abstract : Jayson, M. I. V., Davis, P., Whicher, J. T., and Walters, G. (1976). Annals of the Rheumatic Diseases, 35, 443-445. Serum copper and caeruloplasmin in ankylosing spondylitis, systemic sclerosis, and morphea. Studies of serum copper and caeruloplasmin were performed in patients with ankylosing spondylitis, systemic sclerosis, and morphea. Mean levels of both were raised significantly in ankylosing spondylitis, with the greatest increases in the worst cases. In patients with systemic sclerosis there was a significant increase in the mean level of caeruloplasmin, but not of copper, although both were raised in the 2 patients with the most aggressive disease. No alterations were found in patients with morphea. The values in the patients overlapped considerably with the values in the control subjects. It is thought that the increase in serum copper is probably secondary to the increase in caeruloplasmin which occurs as a nonspecific response to inflammation.